Improving resilience to climate impacts in West Africa through improved availability, access and use of climate information: dialog with users - Ali, Abdou; Djibo, Hamidou; Minoungou, Bernard; Dinku, Tufa; Platzer, Barbara (2014)
The stakeholder workshop on “Improving Resilience to Climate Impacts in West Africa Through Improved Availability, Access and Use of Climate Information: Dialogue With Users” was convened by the Centre Regional de Formation et d'Application en Agrométéorologie et Hydrologie Opérationnelle (AGRHYMET) in collaboration with the International Research Institute for Climate and Society (IRI) with funding and technical support from the United States Agency for International Development (USAID), the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the United Nations Development Program (UNDP). Stakeholders from six Permanent Inter-state Committee for Drought Control in the Sahel (CILSS) countries were invited, in addition to representatives of five river basin organizations and the African Center of Meteorological Application for Development (ACMAD). The three-day meeting in Niamey, Niger (January 21-23, 2014) was attended by 40 participants and facilitators. It consisted of five components: • Introduction to AGRHYMET’s latest climate data, tools, and information products; • Training on the use of the tools for data analysis and visualization; • Engagement on the concept of climate risk management in the different sectors; • Soliciting feedback and needs from participants, to assess the value of the available tools and products to users, and inform improvements that are most relevant to stakeholders; and • Exploration of an Advisory Group for improving Climate Services provided by the AGRHYMET Center. The workshop introduced and solicited feedback on data, products and decision-support tools launched to support improved resilience to climate impacts, across sectors, initially targeting the agriculture, water and disaster risk management communities.